Práticas epistêmicas e argumentação em uma atividade investigativa de física - Freire, Felipe Aragão (2021)
The research presented in this dissertation had as objective to analyze the arguments elaborated by students, along a sequence of investigative teaching of Physics, considering their possible relations with the other epistemic practices and with the epistemic movements developed by the teacher. The research was based on studies by Gregory J. Kelly and collaborators, which represent an empirical program of epistemology, focusing on what counts as knowledge, reasoning, justification and representation in science education contexts. In such studies, epistemic practices are understood as socially organized and interactively realized forms, by which members of a group propose, communicate, evaluate and legitimize claims for knowledge. Argumentation is understood as an epistemic practice whose development, associated with that of other practices, favors students' scientific literacy. To carry out this research, characterized as a case study, a qualitative approach was used; however, quantitative approaches were not disregarded in the analysis, in order to ensure a broader look at the situation investigated. The Investigative Teaching Sequence (IST), composed of 3 classes, was applied to a group of students in the 2nd grade of High School of The College of Application of the Federal University of Sergipe. It was structured with inspiration in the Investigative Cycle proposed by Pedaste et al. and aimed to provide opportunities for students to elaborate explanations and arguments based on evidence about the thermal expansion process of solids. The meetings, held within a virtual platform through videoconferences, were videotaped and, later, went through a transcription process. In addition to these data, it was possible to collect data from didactic material, questionnaires and participatory comments made by students in the chat on the virtual platform. To analyze the students' oral and written arguments, the Toulmin’s Argument Pattern (TAP) was used. Bearing in mind that the SEI structure analyzed preserved the interactive and social space, the possibility of establishing epistemic practices in virtual environments was verified. These, in turn, occurred more frequently in the social instance of knowledge communication. The results obtained also showed that the discussion fostered by the teacher was fundamental for the students' engagement and the development of more structured and complex arguments throughout the SEI.